Audit of Human Resources Management in Vouk Hotel & Suites Bali - Ni Wayan Bunga Niti Rahayu; I B Anom Yasa; P Adi Suprapto (Jurusan Akuntansi Politeknik Negeri Bali, 2021)
Human resource is the main pillar for a company to realize the company’s vision, mission, and goals. This research aimed to assess (evaluate) the programs and resource management system in Vouk Hotel & Suites Bali. The data sources used were primary and secondary data. The primary data source was taken from structured interview and questionnaire distribution, meanwhile the secondary data source was taken from regulation book, standard operating procedure (SOP), percentage absenteeism, and employee service income in 2019 at Vouk Hotel & Suites Bali. The obtained data was analyzed by using descriptive qualitative method with four steps of analysis in audit management, namely: preliminary audit, review and management control testing, follow-up audit, and recommendation. The result of the research indicated the weaknesses of several human resource functions, those are planning, employee training & development, employee performance appraisal, and given compensation. Based on the indicating weakness of the research, therefore, some improvement recommendations were given.